Disease is essentially a biodiversity: A hypothesis. (May 2022) - Chu, Ting; Yang, Maosheng
Abstract: The aim of this article is to understand and reveal the nature of human disease. Evidence from scientific studies indicate that disease may be a kind of biodiversity. Hence, we hypothesize that disease, therefore by its very nature, is a biodiversity. We believe that this hypothesis above may play an important role in creating or leading the new direction for medical development and medical education, and which can be reflected in (1) it is helpful to explain clearly the causes of human diseases and their development process, and has an important significance for the research and development of new prevention and treatment approaches on human disease; (2) it is conducive to cultivating a new generation of medical talents, and promoting the development of medicine; (3) it is helpful to push forward the research and understanding the life phenomena of human beings. Therefore, this idea that disease is essentially a biodiversity should be introduced into the education of medicine, the treatment and prevention of diseases, the research and development of new drugs, the medical research, and the formulation of disease-related laws and regulations.